Economically Rational Expectations: Are Innovations in the Rate of Inflation Independent of Innovations in Measures of Monetary and Fiscal Policy? - Feige, Edgar L.; Pearce, Douglas K. (Journal of Political Economy, 1976)
The concept of "economically rational" expectation formation is developed for a regime in which the acquisition and use of some information sets are nonnegligible. The concept provides a middle ground between "autoregressive" expectation formation and "rational" expectation formation. A necessary condition for the use of nonnegligible cost information sets is that such sets serve as leading indicators or more formally satisfy the causality conditions of Granger (1969). Using a time series modeling identification methodology developed by Box and Jenkins (1970) and Haugh (1972), we test the causal relationship between the rate of inflation and various monetary and fiscal aggregates. Surprisingly, we cannot reject the hypothesis that the rate of inflation is independent of the monetary and fiscal aggregates considered. Since the proposed leading indicator series contain no incremental predictive power once the information contained in the past history of inflation is efficiently utilized, we conclude that autoregressive expectation models may indeed represent economically rational price expectation formation.